Análisis, diseño, desarrollo de un sistema informático para la obtención de indicadores económicos y productivos de sostenibilidad de la producción de leche en fincas del cantón Cayambe. - Salazar Badillo, Diego Iván (2015)
The Web application developed allows keeping track of income, expenses, assets, inventory workers, animal farms and pastures of cattle farms, as well as milk production, this control is carried out by recording the information in a database data that is stored on a server.